Strategi Konten Kreatif Viciety Ambassador dalam Meningkatkan Engagement Media Sosial Instagram - Wina Athifah Zahrah; Bayu Suriaatmaja Suwanda (Lembaga Pengembangan Kinerja Dosen, 2026)
This study is motivated by differences in engagement levels across content posted by Viciety Ambassadors on Instagram. Some posts generate high interactions (likes, comments, shares), while others receive minimal responses despite being created by the same ambassadors. This research aims to analyze the creative content strategies used by Viciety Ambassadors in increasing audience engagement. The study employs a descriptive qualitative approach. Data were collected through observation, in-depth interviews, documentation, and literature review. The findings indicate that engagement is influenced by several factors, including content consistency, message delivery, visual presentation, audience relevance, and adaptation to social media trends. Differences in creative processes and content execution also contribute to variations in engagement outcomes. The study highlights that effective creative content strategies require not only technical skills but also an understanding of audience preferences and platform dynamics. These findings provide both theoretical and practical contributions, particularly for developing more effective content strategies in digital marketing and social media contexts.